Exploring the Chemistry of [2.2.2]Paracyclophane - Lehne, Verena; Ernst, Ludger; Hopf, Henning (Synlett, 2016)
Starting with the parent compound [2.2.2]paracyclophane several routes were developed to synthesize its 4-vinyl derivative. From the 4-aldehyde and the bromomethyl derivative the stilbenophanes were prepared which photocyclize to the phenanthrenophanes. A new route to a bridged ketone was developed which was subjected to the addition of phenyllithium and to typical aromatic substitution reactions (inter alia Rieche formylation, Friedel–Crafts acylation). Bromination of the bridged ketone yielded an unusual tropone derivative. Electrophilic substitution reactions were also carried out for the bridged hydrocarbon, the reduction product of the bridged ketone. For both the bridged ketone and the bridged hydrocarbon the electrophilic substitutions occur regioselectively, favoring the introduction of the new substituent in a syn orientation to the bridging keto and methylene group, respectively.1 Introduction2 Results and Discussion2.1 4-Vinyl[2.2.2]paracyclophane (5)2.2 [2.2.2]Paracyclophane (2a) as Part of Extended Aromatic Systems2.3 The Preparation of 5,12-Methano[2.2.2]paracyclophan-25-one (3)2.4 Selected Reactions with 5,12-Methano[2.2.2]paracyclophan-25-one (3)2.4.1 Reactions of 3 with Metalorganic Reagents2.4.2 Friedel–Crafts Reactions with 32.4.3 Bromination of 32.5 Selected Reactions with 5,12-Methano[2.2.2]paracyclophane (31)2.5.1 Friedel–Crafts Reactions2.5.2 Bromination of 313 Conclusion
Keywords: cyclophanes; electrophilic aromatic substitution; bromination; Rieche formylation; Friedel–Crafts acylation; photocyclization; McMurry coupling